Etude comparative de trois variétés de fève (AGUADULCE, LUZ DE OTONO et REINA MORA) pour les rendements en vert pour le marché et en sec pour la production de semence. - DOUBA, FATIMA (My University, 2016)
The objective of This Works is a contribution to the study of behavior of three varieties of imported beans Reina Mora, Luz de otono and Super Aguadulce. The work was the study of characters such as lifting, flowering and finally performance; green for the market and Dry for multiplication and seed production. The results show the potential of the Super variety Aguadulce and better provisions for the market and especially for the development of the seed market (244.63quintals / ha and 46.43 quintals / ha dry) Then come Luz otono and Reina Mora with respectively returns of (137.57 quintals / ha-118.62quintals/ha and 33.16quintals / ha – 28.29quintals/ha in dry.
Keywords: Bean; Payoff; seed production.; Fève; rendement; production de semences